ISO, via Upregulating MiR-137 Transcription, Inhibits GSK3β-HSP70-MMP-2 Axis, Resulting in Attenuating Urothelial Cancer Invasion - Xirui Guo; Haishan Huang; Honglei Jin; Jiheng Xu; Sanjiv Risal; Jingxia Li; Xin Li; Huiying Yan; Xingruo Zeng; Lei Xue; Changyan Chen; Chuanshu Huang (Elsevier, 2018)
Our most recent studies demonstrate that miR-137 is downregulated in human bladder cancer (BC) tissues, while treatment of human BC cells with isorhapontigenin (ISO) elevates miR-137 abundance. Since ISO showed a strong inhibition of invasive BC formation in the N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN)-induced invasive BC mouse model, the elucidation of a potential biological effect of miR-137 on antagonizing BC invasion and molecular mechanisms underlying ISO upregulation of miR-137 are very important. Here we discovered that ectopic expression of miR-137 led to specific inhibition of BC invasion in human high-grade BC T24T and UMUC3 cells, while miR-137 deletion promoted the invasion of both cells, indicating the inhibitory effect of miR-137 on human BC invasion. Mechanistic studies revealed that ISO treatment induced miR-137 transcription by promoting c-Jun phosphorylation and, in turn, abolishing matrix metalloproteinase-2 (MMP-2) abundance and invasion in BC cells. Moreover, miR-137 was able to directly bind to the 3' UTR of Glycogen synthase kinase-3β (GSK3β) mRNA and inhibit GSK3β protein translation, consequently leading to a reduction of heat shock protein-70 (HSP70) translation via targeting the mTOR/S6 axis. Collectively, our studies discover an unknown function of miR-137, directly targeting the 3' UTR of GSK3β mRNA and, thereby, inhibiting GSK3β protein translation, mTOR/S6 activation, and HSP70 protein translation and, consequently, attenuating HSP70-mediated MMP-2 expression and invasion in human BC cells. These novel discoveries provide a deep insight into understanding the biomedical significance of miR-137 downregulation in invasive human BCs and the anti-cancer effect of ISO treatment on mouse invasive BC formation. Keywords: miR-137, GSK3β, ISO, HSP70, MMP-2, bladder cancer